Preacher. Season 2 [videorecording (DVD)] - Goldberg, Evan; Rogen, Seth, 1982-; Cooper, Dominic, 1978-; Gilgun, Joe, 1984-; Negga, Ruth, 1982- (Sony Pictures Home Entertainment, 2017)
Follows the adventures of a Texas preacher whose body is inhabited by a mysterious entity that gives him supernatural powers.